Fast Check for Laterally Supported Beam Capacity - Odeh, M. David (Engineering Journal, 1984)
The purpose of this article is to arrive at a "rule of the thumb" method to determine the total uniform load capacity of a laterally supported simple beam, with the only known data being (a) steel beam designation and (b) span. No other data or references are required. It was found through analysis that the section properties of any rolled steel beam section are "built into" the beam designation, i.e. depth and weight.